Characteristics of Millennial Farmers in East Priangan West Java - Indonesia - Rusmono, Momon; Effendy, Lukman; Azzahra, Fatimah (Technium Sustainability, 2024)
A research on the character of millennial farmers has been carried out in West Java covering Garut, Tasikmalaya, and Ciamis Regencies. The research objectives: (1) describe the characteristics of millennial farmers, (2) find the dominant factors that characterize millennial farmers, and (3) find a model for increasing the role of millennial farmers in agricultural development. The research approach is in the form of a survey of 72 samples determined based on a quota of 30 percent of the population. Data were collected through direct interviews using a closed questionnaire containing statements that have provided four answer options with a score of 1 - 4. Before being used, the questionnaire was first tested for validity and reliability with the results including being eligible to be used as a data collection tool. The collected data is analyzed in two ways; descriptive statistics and Partial Least Square (PLS) analysis. The results of the study found: (1) the character of millennial farmers in the East Priangan region of West Java is the category of productive age (31-60 years), relatively less experienced in farming; have high technical competence including: the ability to choose commodities, technical cultivation skills, the ability to utilize social media, and the ability to use digital applications; have adequate managerial competence, including: ability in business management, building cooperative networks, ability to manage resources, but less able to resolve conflicts; and has social competence such as having the ability to develop community education, economy, and development programs, but lacking in managing community organizations; (2) the character of millennial farmers is determined by technical competence, managerial competence, and social competence, as well as individual characteristics, especially age and experience; (3) the character of millennial farmers has a positive impact on the growth of young agropreneurs and food security